The New Way: How to Achieve Indonesia Higher Economic Growth in 2020 - Rizal Ramli (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
Rizal Ramli, a prominent national figure, senior technocrat and economist, argues that the government must reverse the logic built so far: Indonesia must first increase its economic growth to above 7%, then investment will surely come again. This paper is a his view of the economic conditions of the Jokowi era and how to rebuild Indonesia's economy going forward to rise from an alarming slump So far, he argues, deindustrialization has accelerated in the Joko Widodo era. The setback is marked by growth in the manufacturing industry sector until the third quarter of 2018 was 4.3% slower than the growth in the same period in 2017 at 4.8% and the processing industry growth rate is 4.3%, lower than the economic growth rate of 5%.